A miniature origami biofuel cell based on a consumed cathode. Issue 92 (2nd November 2016) - Yu, You; Han, Yujie; Lou, Baohua; Zhang, Lingling; Han, Lei; Dong, Shaojun
Abstract : A miniature origami BFC has been fabricated from a MnO2 –graphite flake consumed solid-state cathode. Abstract : Considerable interest has been focused on miniature biofuel cells (BFCs) because of their portability and possibility to be implantable. Origami devices with hollow channels will provide novel insight into the assembly methods of miniature BFCs. Herein a miniature origami BFC has been fabricated from a MnO2 –graphite flake consumed solid-state cathode. For further practical applications, miniature origami BFCs can directly generate energy from soft drinks.